DESIRE UNDER THE ELMS AND THE EMPEROR JONES ARE A PICTURES OF TRAGIC CONFLICT BY EUGENE O’NEILL IN MODERN AMERICAN DRAMA - Ibrahim, Haider; Nawi, Abdullah Mohd; Ali, Ansam (International Journal of Psychosocial Rehabilitation, 2020)
This paper aims to study Desire Under the Elms and The Emperor Jones are the pictures of conflict. The dramatist, O’Neill wants to reveal the struggles and conflict in the selected plays. This conflict leads to the tragedy in modern American drama. The researchers use the qualitative method, the narrative analysis as the storytelling techniques. The study uses the conflict theory by Karl Marx (1888-1818) to justify the conflict or the struggle in the plays of O’Neill to tackle the characters, the actions and plot.